Construction of complementary sequence sets based on complementary pairs. Issue 18 (1st July 2020) - Pai, C.‐Y.; Chen, C.‐Y.
Abstract : In this Letter, a new construction of complementary sequence sets (CSSs) is proposed by concatenating Golay complementary pairs (GCPs) which could have different lengths. The constructed CSSs have flexible sequence lengths, i.e. 2 L + N, where L and N are the lengths of two constituting GCPs. For example, the proposed method can be used to construct quadriphase CSSs of all lengths up to 100, except 87 and 95. The feasibility for practical applications of CSSs will be enhanced due to their flexible lengths and good peak‐to‐average power ratio property.